2002
DOI: 10.1007/s00228-002-0493-y
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reactions and cognitive function among hospitalized older adults

Abstract: Cognitive impairment is associated with a lower detection rate of ADRs, and it represents a confounder of the association between age and ADRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 35 publications
2
36
0
2
Order By: Relevance
“…In keeping with our findings, it has been suggested that patients with dementia tend to underreport common symptoms compared to nondemented subjects [43] and physicians underdiagnose ADEs in patients with cognitive impairment [15] . It has also been suggested that demented patients may be evaluated less carefully by physicians leading to an underestimation of ADEs in this population [44] and that neuropsychiatric ADEs associated with psychotropic medications can be underrecognized leading to increased psychotropic use [45] .…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In keeping with our findings, it has been suggested that patients with dementia tend to underreport common symptoms compared to nondemented subjects [43] and physicians underdiagnose ADEs in patients with cognitive impairment [15] . It has also been suggested that demented patients may be evaluated less carefully by physicians leading to an underestimation of ADEs in this population [44] and that neuropsychiatric ADEs associated with psychotropic medications can be underrecognized leading to increased psychotropic use [45] .…”
Section: Discussionsupporting
confidence: 77%
“…Cognitive function as a risk factor for ADEs has also been a subject of debate with both increased [37,41] and decreased risk [15] being described. In keeping with our findings, it has been suggested that patients with dementia tend to underreport common symptoms compared to nondemented subjects [43] and physicians underdiagnose ADEs in patients with cognitive impairment [15] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Second, adverse drug effects (ADEs) are common in patients with dementia, 2730 yet ADEs are difficult to detect by clinicians because these patients have difficulty expressing the symptoms they feel. 31,32 Third, this population has frequent clinical complications associated with a high risk of 6-month mortality, and the time to benefit from many medications exceeds this life expectancy.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a number of these risks were not found to be significant predictors of ADR in this current study. For example, well known factors such as age [23], previous history of ADR, gender [24], heart failure [8], prior bleeding on admission [25], renal impairment [26], the use of certain drug classes [27], and abnormalities in certain laboratory parameters [6] were not retained in our final model. The omission of these previously identified risk factors could possibly be explained by the inclusion criteria, which recruited a broader range of ages.…”
Section: Discussionmentioning
confidence: 99%